Clinically significant anatomical variation of the retropharyngeal internal carotid arteries - Jaskirat K. Gill, MD (Radiology Case Reports, 2017)
Although interpatient variations in the course and anatomy of extracranial internal carotid arteries (EICAs) have been described previously, intrapatient variability is rarely cited in the literature. Distance between EICAs and the pharyngeal wall is an important determinant of vascular injury risk. A retropharyngeal EICA has crucial implications in patients undergoing pharyngeal procedures, and important in otorhinolaryngology and emergency medicine. Surgical exploration without identification of anatomical landmarks, or emergent intubation in the emergency room poses high risk for EICA injury. Other critical clinical considerations include intra-arterial involvement of tonsillitis, peritonsillar abscesses, or parapharyngeal neoplasms due to close proximity to the EICA. We present 2 cases with short-term change in retropharyngeal course of EICA to highlight this further. Although no clear etiology for these changes has been identified, we hypothesize that embryology, weight alterations, atherosclerotic disease, and postradiation changes are contributory. Thus, one radiologic study does not exclude variation in vascular anatomy.